THE TEACHING OF ENGLISH PRONUNCIATION FOR STUDENT TEACHER: A CASE STUDY IN DESA INGGRIS SINGOSARI, MALANG (RETAIN, 2016)
THE TEACHING OF ENGLISH PRONUNCIATION FOR STUDENT TEACHER: A CASE STUDY IN DESA INGGRIS SINGOSARI, MALANG Astrit Maria English Education Department, Faculty of Languages and Arts, State University of Surabaya astritmaria@mhs.unesa.ac.id Lies Amin Lestari English Education Department, Faculty of Languages and Arts, State University of Surabaya lies.aminlestari@gmail.com Abstrak Dalam pengajaran bahasa Inggris, kemampuan baik guru dalam berbicara merupakan sarana bagi siswa untuk memahami baik contoh penggunaan bahasa maupun instruksi yang disampaikan guru dalam bahasa Inggris. Pentingnya berkemampuan bicara yang baik berhubungan dengan bagaimana guru melafalkan ucapan dengan jelas untuk menghindari kesalahpahaman. Bullough (1997) memastikan bahwa pelafalan berpengaruh pada kemajuan guru secara mendalam dengan cara menggunakan bahasa Inggris secara konsisten. Meski begitu, pengajaran pelafalan seringkali diabaikan dan tidak dianggap penting. Oleh karena itu, penelitian ini menjelaskan pengajaran pelafalan bahasa Inggris di Desa Inggris Singosari, Malang yang menghasilkan peningkatan siswa dalam pelafalan bahasa yang jauh lebih baik. Penelitian ini fokus pada teknik dalam mengajar dan deskripsi pengucapan siswa, sehingga metode campuran dari penelitian kualitatif diterapkan dengan melibatkan 3 peserta yang mewakili kelas BeTe; seorang guru bahasa Inggris dan dua siswa. Penelitian ini bertujuan untuk mengetahui teknik yang diterapkan dan kinerja pelafalan siswa setelah mengalam teknik – teknik terapan tersebut dalam satu semester. Untuk mengetahuinya, beberapa pengamatan dan wawancara mendalam dilakukan. Terbukti dari hasil temuan bahwa guru menerapkan sembilan teknik penting yang berdampak pada peningkatan siswa terhadap kinerja pelafalan. Hal ini berarti bahwa pelafalan siswa menjadi lebih baik setelah mengikuti kelas BeTe. Berdasarkan teori-teori yang ada, teknik yang diterapkan guru tersebut terbukti berlaku untuk kelas pelafalan pada umumnya. Oleh karena itu, kesimpulannya adalan temuan dari penelitian ini dapat menjadi acuan terpercaya baik untuk pengajaran pelafalan maupun penelitian lebih lanjut. Kata Kunci: pengajaran pelafalan, pelafalan bahasa, teknik dalam mengajar, siswa keguruan, institusi bahasa. Abstract In English language teaching, teacher’s good speech is a means for students to comprehend both the language example and the instruction that the teacher conveys using English. The need to conduct good speech deals with how the teacher can pronounce the utterance clearly to avoid miscomprehension. Bullough (1997) determined that pronunciation impacts on the teacher’s personal improvement by using the language consistently. Even so, the teaching of pronunciation is primarily disregarded and not considered a necessity. Therefore, this study explicated the teaching of English pronunciation in Desa Inggris Singosari, Malang that manages to result the students’ improvement of far better pronunciation performance. This study focused on the techniques in teaching and the description of the students’ pronunciation, that mixed methods of qualitative research were applied by engaging 3 participants that represent the class of BeTe; an English teacher and two student teachers. This research dealt with the need to figure out the applied techniques and the students’ pronunciation performance after experiencing the techniques for a semester. To figure those out, some observations and in-depth interviews were conducted. The findings verified that the teacher commonly applied nine valuable techniques which impact on the students’ improvement on the pronunciation performance. It can mean that the students’ pronunciation goes better after experiencing BeTe. Based on the existed theories, the techniques by the teacher are proven applicable for the prevalent pronunciation class. Hence, it implies that the findings of the current study can be the dependable reference both for the teaching of pronunciation and further research. Keywords: teaching pronunciation, pronunciation, techniques in teaching, student teacher, language institution.